Grapevine Rpv3-, Rpv10- and Rpv12-mediated defense responses against Plasmopara viticola and the impact of their deployment on fungicide use in viticulture - Wingerter, Chantal; Eisenmann, Birgit; Weber, Patricia; Dry, Ian; Bogs, Jochen (BMC plant biology, 2021)
The high susceptibility of European grapevine cultivars (Vitis vinifera) to downy mildew (Plasmopara viticola) leads to the intensive use of fungicides in viticulture. To reduce this input, breeding programs have introgressed resistance loci from wild Vitis species into V. vinifera, resulting in new fungus-resistant grapevine cultivars (FRC). However, little is known about how these different resistance loci confer resistance and what the potential reduction in fungicide applications are likely to be if these FRCs are deployed. To ensure a durable and sustainable resistance management and breeding, detailed knowledge about the different defense mechanisms mediated by the respective Rpv (Resistance to P. viticola) resistance loci is essential.
Gesehen am 15.12.2021